Extracraniofacial anomalies in craniofacial microsomia: retrospective analysis of 991 patients. Issue 9 (September 2019) - Renkema, R.W.; Caron, C.J.J.M.; Pauws, E.; Wolvius, E.B.; Schipper, J.A.M.; Rooijers, W.; Dunaway, D.J.; Forrest, C.R.; Padwa, B.L.; Koudstaal, M.J.
Abstract: Craniofacial microsomia (CFM) is characterized by unilateral or bilateral underdevelopment of the facial structures arising from the first and second pharyngeal arches, but extracraniofacial anomalies may also be present. This retrospective study provides an overview of the prevalence, types, and characteristics of extracraniofacial anomalies in patients with CFM. All patients diagnosed with CFM seen at four craniofacial centres were included. The patient charts were reviewed and data on patient characteristics and extracraniofacial anomalies were extracted. Of the 991 patients included, 462 (47%) had extracraniofacial anomalies. The prevalence of extracraniofacial anomalies in the various tracts was as follows: vertebral 28%, central nervous system 11%, circulatory system 21%, respiratory tract 3%, gastrointestinal tract 9%, and urogenital tract 11%. Compared to patients without extracraniofacial anomalies, those with an extracraniofacial anomaly were at higher risk of having additional extracraniofacial anomalies in other tracts. The prevalence of extracraniofacial anomalies was greater in patients with bilateral CFM, a more severe mandibular deformity, or facial nerve or soft tissue deformity. Patients with CFM should be screened for extracraniofacial anomalies by physical examination with specific attention to the circulatory, renal, and neurological tracts. Diagnostically, electrocardiography, echocardiography, spine radiography, and renal ultrasound should be performed for patients at risk of extracraniofacial anomalies.